2009
DOI: 10.3144/expresspolymlett.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of agglomeration effects in multi-walled carbon nanotube-polycarbonate melts

Abstract: Abstract. In this study we report on morphological and rheological characterization of multi-walled carbon nanotube (MWNT)-polycarbonate composites produced by injection molding. The main focus is to carry out nonlinear viscoelastic experiments that allow following the structural rearrangements of carbon nanotubes in the polycarbonate melt. Small angle X-ray scattering reveals only a slight orientation of MWNTs in the as-received samples, i.e. after application of extremely high shear rates. Thus, the main str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…A region where moduli are independent of strain amplitude then appears with increasing amplitude, extending to strains beyond 10 % strain for the unfilled PC, but only to 0.5 % strain for the filled PC. The earlier onset of nonlinearity has been previously attributed to the effect of strain amplification: the matrix experiences a higher local strain than the macroscopic strain due to the presence of the stiff nanotubes (Richter et al 2009;Costa et al 2008). This effect is generally enhanced by confinement of polymer chains located near the surface of a nanotube (Stöckelhuber et al 2011;Vilgis 2005).…”
Section: Resultsmentioning
confidence: 95%
“…A region where moduli are independent of strain amplitude then appears with increasing amplitude, extending to strains beyond 10 % strain for the unfilled PC, but only to 0.5 % strain for the filled PC. The earlier onset of nonlinearity has been previously attributed to the effect of strain amplification: the matrix experiences a higher local strain than the macroscopic strain due to the presence of the stiff nanotubes (Richter et al 2009;Costa et al 2008). This effect is generally enhanced by confinement of polymer chains located near the surface of a nanotube (Stöckelhuber et al 2011;Vilgis 2005).…”
Section: Resultsmentioning
confidence: 95%
“…In the case of random orientation distribution of rod-like inclusions one obtains the isotropic conductivity of composite which is proportional to the isotropic matrix conductivity with the coefficient of proportionality given by Equation (2). Fitting the viscoelastic data for the same MWNTpolycarbonate composite, we found that the average aspect ratio of the multi-wall carbon nanotubes is about 40 [42]. This value roughly corresponds to the ratio of the Kuhn segment length, reported for the carbon nanotubes to be about 1 !m [45], to the nanotube diameter (13-16 nm).…”
Section: Model Description 31 Electrical Conductivitymentioning
confidence: 82%
“…to the conditions relevant for nanocomposite processing. Theoretical predictions at the temperature of 340°C, which was found to be optimal for the injection moulding of MWNT/polycarbonate melts [42], are shown on the same Figures 5a and 5b as a black solid line. Additionally, on Figure 5d we present the model predictions for the system with 5 wt% MWNTs at three melt temperatures (265, 295 and 340°C).…”
Section: Steady-state Electrical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes orientation in the final nanocomposite and agglomeration effect appearing during injection molding has been investigated with rheology tests showing the indication of nanofiller alignment sensitivity to the high shear conditions. [103] Visco-elastic properties of matrix in presence of nanofiller network is strongly related to CNT re-agglomeration process. Various methods are used to carry out such functionalization, with the use of main types polymerizations including ionic, [110][111][112] redox [113] and metallocene catalysis [114][115] as well as electrochemical grafting [116] used widely e.g.…”
Section: Injection Molding Of Nanocompositesmentioning
confidence: 99%